Association of Single-Nucleotide Polymorphisms With Chronic Rhinosinusitis in a Southwestern Han Chinese Population: A Replication Study. Issue 3 (May 2020) - Xu, Yang; Zheng, Yongbo; Cao, Min; Yang, Wen; Ren, Jianjun; Song, Yao; Cheng, Danni; Wang, Jing; Huang, Ligao; Xu, Wei; Zhao, Yu; Liu, Geoffrey
Background: Chronic rhinosinusitis (CRS) is a multifactorial inflammatory disease. The role of genetic variations of related genes in the development of CRS and severity of symptoms is unknown in Southwestern Chinese populations. Objective: We selected candidate CRS-related genetic polymorphisms and evaluated the associations that were different according to the presence of nasal polyp, asthma, and allergic rhinitis (AR) in a Southwestern Chinese population. Detailed phenotypes were compared among different genotypes. Methods: In 452 CRS patients and 591 healthy controls, clinico-epidemiological information was collected and 23 previously reported CRS-related single-nucleotide polymorphisms (SNPs) were genotyped. Genotypes were determined using a Sequenom MassARRAY SNP genotyping system. Clinical disease measures including the sinonasal outcome test, visual analogue scale (VAS), and symptom severity VAS were evaluated for each patient. The association between CRS, genotypes, asthma, AR, and symptoms was analyzed. The effect of sex, age, body mass index, and status of smoking was considered. Results: Statistically significant genotypic association with CRS was observed with an IL1RL1 genetic polymorphism (rs13431828; odds ratio [OR] = 1.45; 95% confidence interval [CI], 1.06–1.99; P  = .02). Similar association was observed with rs13431828 in subgroups of CRS with nasal polyps (OR = 1.53; 95% CI, 1.03–2.29; P  = .04), asthma (OR = 2.08; 95% CI, 1.14–3.79; P  = .02), and AR (OR = 1.59; 95% CI, 1.06–2.39; P  = .02). No significant association with other SNPs was observed. The evaluated genetic polymorphisms were not associated with clinical symptom scores. Conclusion: This study replicated rs13431828 as being associated with CRS in Southwestern Chinese. rs13431828 was also significantly associated with CRS patients who have concurrent allergic nasal diseases.